2021
DOI: 10.1530/jme-20-0250
|View full text |Cite
|
Sign up to set email alerts
|

ACOX1, regulated by C/EBPα and miR-25-3p, promotes bovine preadipocyte adipogenesis

Abstract: Acyl-Coenzyme A oxidase 1 (ACOX1) is the first and rate-limiting enzyme in peroxisomal fatty acid β-oxidation of fatty acids. Previous studies have reported that ACOX1 was correlated with the meat quality of livestock, while the role of ACOX1 in intramuscular adipogenesis of beef cattle and its transcriptional and post-transcriptional regulatory mechanisms remain unclear. In the present study, gain-of-function and loss-of-function assays demonstrated that ACOX1 positively regulated the adipogenesis of bovine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…miRNAs can directly target mRNAs to regulate gene expression and often interact with mRNAs and ncRNAs through the ceRNA network to play regulatory roles [50]. Through differential expression and functional enrichment analyses, we identified many miRNAs, including miRNA-30c [51], miR-25-3p [52] and miR-23a ~ 27a ~ 24-2 [53], that have been found to target key genes to regulate human and bovine adipogenesis. More importantly, our results revealed several potential ceRNA regulatory networks during bovine intramuscular preadipocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs can directly target mRNAs to regulate gene expression and often interact with mRNAs and ncRNAs through the ceRNA network to play regulatory roles [50]. Through differential expression and functional enrichment analyses, we identified many miRNAs, including miRNA-30c [51], miR-25-3p [52] and miR-23a ~ 27a ~ 24-2 [53], that have been found to target key genes to regulate human and bovine adipogenesis. More importantly, our results revealed several potential ceRNA regulatory networks during bovine intramuscular preadipocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Other reports have studied CoA in the process of β-oxidation and found that Nudt7 and Nudt19 in the Nudt superfamily can exert positive effects on CoA substrates in certain metabolic processes to promote the metabolic process [115,116]. With the upsurge of research on noncoding RNAs (ncRNAs), some play positive or inhibitory roles in peroxisomal β-oxidation, such as miR-222, miR-25-3p, circ_0005379, and others [117][118][119][120][121][122], which mainly target the rate-limiting enzyme ACOX1. Recently, Li et al analyzed the ACOX1 transcript and found that miR-532-3P could regulate the expression of ACOX1 by targeting the complementary sequence in the 3'-UTR, thereby participating in lipid metabolism [117].…”
Section: Othersmentioning
confidence: 99%
“…CPT2 (carnitine palmitoyltransferase-2), catalytic fatty acid transport to mitochondria for B oxidation during fat oxidation, may CPT2 and ACADL be positive synergistic [12]. Acyl-Co A Oxidase 1, ACOX1) is a rate-limiting enzyme for the first step of dehydrogenation of fatty acid β-oxidation in the peroxisome, which specifically catalyzes the dihydroxylation of long-chain and very long-chain fatty acids to form trans double-bonded double α, β-aleno-lipoyl-CoA, and studies have reported that after overexpression of ACOX1, fat cell differentiation is inhibited [13],…”
Section: Discussionmentioning
confidence: 99%